La actuación política de los docentes primarios durante la “Revolución Argentina”. Un análisis sobre características y alcances de la protesta gremial entre 1968 y 1972 - Mariana Gudelevicius (Nuevo mundo - Mundos Nuevos, 2011)
The article presents/displays advances of an investigation in course on the particularitities of educational trade union protest of primary level in a conflicting process as he were it the one of 1966-1973 in Argentina. From the analysis of the political action of the educators in the dictatorial context of the “Argentina Revolution, the objective is, on the one hand, to investigate in what it can say on the teaching, the formulated characteristics of its concrete practices, requests, strategies of fight, positionings. On the other, the effects that these produce so much in the political sand as in their own configuration like historical subject.